Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Volume - VI General Areas Government of Assam - Planning Commission (Planning Commission, 1985)
The Government of Assam are also fully committed to the development, of Science & Technology within the framework of the National Science & Technology Policy and the guidelines laid down in the twenty point programme. This region is comparatively backward in the field of Science & Technology compared to the rest of the country. The Science & Technology will be promoted to play a major role in improving the quality of life, specially of those, who have so far not been able to enjoy the benefits of the developmental process taking place in the country.
Planning and Development Department, Government of Assam